Identitas Yesus Sebagai Anak Allah Menurut Lukas 3:21-22 - Liberatus Mayabubun; Johanis Luturmas (Sekolah Tinggi Filsafat Seminari Pineleng, 2022)
This essay discusses the identity of Jesus as the Son of God according to Luke 3:21-22. By using the historical-critical method, the author intends to underline the main message of Luke 3:21-22 that witnesses Jesus Christ as the Son of God. His identity comes from God Himself. At the baptism in the Jordan river, God declared before many people that Jesus was His beloved Son. The identity of Jesus as the Son of God reveals a special relationship between Jesus and His Father. The relationship is not a biological relationship between father and son, but a divine one. Jesus is the Son of God who was anointed to bring salvation to mankind.